3D-Printed Surgical Guiding System for Double Derotational Osteotomy in Congenital Torsional Limb Deformity: A Case Report. Issue 1 (January 2021) - Sabatini, Luigi; Nicolaci, Giulia; Giachino, Matteo; Risitano, Salvatore; Pautasso, Andrea; Massè, Alessandro
Abstract : Case: A 19-year-old woman with persistent anterior knee pain was diagnosed with a complex tibial and femoral torsional deformity (26° of femoral anteversion and 49° of tibial external rotation). To achieve the correct realignment of the lower limb, rotational double osteotomies were needed. After planning the correction on the computed tomography scan and three-dimensional (3D) model, a custom-made 3D-printed guiding system was produced to support the surgery. Conclusion: The 3D-printed planning model and the surgical guiding system are crucial elements to achieve optimal results for complex malalignment cases. The "tailored" guides led to a perfect match between the planned correction and the intraoperative result.